2006
DOI: 10.1590/s1413-35552006000200009
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da amplitude articular do joelho: correlação entre as medidas realizadas com o goniômetro universal e no dinamômetro isocinético

Abstract: RESUMOContextualização: O instrumento mais utilizado pelos terapeutas para mensuração da amplitude de movimento (ADM) articular é o goniômetro universal. No entanto, há carência de estudos que analisem a confiabilidade das medidas da ADM do joelho realizadas no dinamômetro isocinético. Objetivo: O objetivo deste estudo foi analisar a correlação entre as medidas de ADM na articulação do joelho, realizadas com o goniômetro universal e no dinamômetro isocinético. Método: Foram avaliados 38 voluntários saudáveis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
14

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 18 publications
1
4
0
14
Order By: Relevance
“…We found that both methods are reproducible and highly correlated for the measured movements. Our findings are supported by previous results using UG 1,2,6 . Photogrammetry is a reliable method for postural analysis and has been increasingly used to obtain specific measures of joint angles 17 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that both methods are reproducible and highly correlated for the measured movements. Our findings are supported by previous results using UG 1,2,6 . Photogrammetry is a reliable method for postural analysis and has been increasingly used to obtain specific measures of joint angles 17 .…”
Section: Discussionsupporting
confidence: 93%
“…It is essential for establishing physiotherapeutic diagnosis, as well as estimating and quantifying the effectiveness of therapeutic intervention, therefore measuring the progress of rehabilitation [1][2][3] . Different methods for measuring ROM are available, ranging from visual inspection to the use of precision tools and computer-assisted estimates.…”
Section: Introductionmentioning
confidence: 99%
“…They were also advised to stop the dynamometer resistance arm using the device as soon as they felt the beginning of knee flexor muscular tension in stretching, which occurred normally between 90° and 20° of knee extension for the subjects who were selected, could not perform total knee extension (0°). The measurements were taken three times and the mean value was used for the statistical analysis 14 . No warm-up was performed before the measurement of the amplitude of movement.…”
Section: Methodsmentioning
confidence: 99%
“…Então foram realizadas, com marcações adesivas, marcações nas seguintes estruturas: trocânter maior do fêmur, epicôndilo femoral lateral e maléolo lateral do membro que foi avaliado. O quadril foi mantido nesta posição e o primeiro avaliador realizou a extensão passiva do joelho direito até que o indivíduo referisse desconforto para completar a amplitude do movimento 7 . Neste momento, anotou-se a angulação obtida na extensão do joelho.…”
Section: Goniômetro Universalunclassified